Kualitas Bakteriologis Sumber Mata Air Mumbul Sari Kabupaten Lombok Utara - Fauzi Mahendra; Nining Purwati; Dadan Supardan (Bioscientist : Jurnal Ilmiah Biologi, 2022)
Water is the main and most important need for living things. The water consumed must meet the physical, chemical, bacteriological requirements, and be free from Coliform bacteria contamination. This research is a qualitative descriptive study that aims to determine the bacteriological quality of the spring water in the Mumbul Sari Village community, Bayan District, North Lombok Regency. The data collection technique used a filter membrane with Colony Forming Units (CFU/100ml). The research data were analyzed descriptively. The results showed that the Mumbul Sari spring in North Lombok Regency was contaminated with Coliform and Escherichia coli bacteria with values exceeding the quality standards set by the Ministry of Health of the Republic of Indonesia. The MPN Coliform value of springs used by women is higher than that of springs used by men (300 CFU/100ml > 250 CFU/100 ml). Similarly, the number of Escherichia coli bacteria (50 CFU/100ml > 12 CFU/100ml).